Analisis Kebutuhan Pelatihan Tenaga Kerja Bagasi di Terminal Penumpang Pelabuhan Makassar - Oktavera Sulistiana; Isnen Rajadiharta; Dewi Usabeni (Hengkara Majaya, 2023)
Training Need Analysis (TNA) or training needs analysis which is a reflection of the actual situation faced by prospective trainees in carrying out their work/tasks. In analyzing training needs, try to compare the results of the current work (performance) that they are doing with what is desired (expected performance) according to predetermined operating standards. This study used a descriptive method, classified into 2 groups of data, namely qualitative and quantitative/Mixed Methods. baggage/baggage labor, and 308 respondents from 500 users of baggage labor services using random sampling technique. The method of data analysis in this study uses descriptive analysis techniques. The results of the study show that the perceptions of service users regarding baggage labor services at the Port of Makassar are generally in the good category, but in terms of security, order and ease of response, doubtful is in second place, greater than the response of strongly agreeing to these two aspects. The perception of baggage workers on the six aspects measured in transportation services is good in general, but if we look in more detail based on several anomaly choices, the safety aspect needs to be given more attention because 29.88% chose not suitable, 29.19% chose doubtful and only 25.19% conform. The training needs needed to improve baggage worker services at Makassar Port are regarding safety with K3 material, security and order with ISPS Code material, convenience and comfort with Service Culture and Customer Satisfaction material.